DIGITAL TECHNOLOGIES OF ACCOUNTING AND ANALYTICAL SUPPORT AND ECONOMIC CONTROL OF OUTSOURCING AND CONSULTING ACTIVITIES OF ENTERPRISES - Balaniuk , I. F.; Sas, L. S.; Kuzmin , T. L.; Smushak , M. V. (The actual problems of regional economy development, 2024)
The article is aimed at researching the key aspects of using digital technologies to optimize accounting and analytical support and economic control in the outsourcing and consulting spheres of enterprise activity. The purpose of the article is to study the use of digital technologies in outsourcing and consulting for accounting, analysis and economic control. To achieve the goal, the article uses research methods, namely: induction and deduction – to determine the main advantages of each type of digital technologies for accounting, analysis and economic control; system analysis – for the study of accounting and analytical processes in their relationship with the system of digital technologies; synthesis – to generalize different aspects of digital technology research in outsourcing and consulting for accounting and analytical support and economic control; abstraction – to form conclusions and recommendations; graphic – for visual display of research results. The article determines that the new digital paradigm has an impact on the accounting and analytical provision of outsourcing and consulting activities of enterprises in various areas: digital solutions, accounting and analytical tasks and software. The main components of digital technologies in economic control are also highlighted, which include financial management systems, automated data analysis tools, cloud computing, blockchain technology, and machine learning and artificial intelligence tools. The scientific novelty of the study is the grouping and definition of the main capabilities of digital technologies for accounting and analytical support and economic control of outsourcing, consulting activities of enterprises. The results of the scientific process can be used by outsourcing and consulting companies during their activities.